(untitled) (Annals of Medical Research, 2022)
Aim: Magnetic Resonance Imaging (MRI) is used to evaluate response in neoadjuvant treatment of rectal cancer, and the predictive value of MRI results is important for clinical decisions. The neoadjuvant rectal cancer (NAR) score is the most commonly used score developed for this purpose. This study aimed to evaluate the power of the NAR score in predicting prognosis in patients with locally advanced rectal cancer who received neoadjuvant chemoradiotherapy treatment in two different centers. Materials and Methods: The data of 85 patients diagnosed with locally advanced rectal cancer who received neoadjuvant chemoradiotherapy and whose treatment-follow-up information can be accessed were evaluated retrospectively, and NAR scores were calculated. Patients were divided into two groups according to NAR score (score ≤16 and patients with> 16), and overall survival (OS) and disease-free survival (DFS) results were compared. Results: The median follow-up was 25 (1.3-56) months from the end of RT. The 13 patients died, 72 patients were alive, and relapse was observed in 25 patients. Patients’ median OS was 28 months (range 4-59), median DFS was 24 (1-59) months. In patients with NAR ≤16, median OS was 27 (3-59) months; in patients with NAR>16, median OS was 24 (5-54) months (0.057). In patients with NAR ≤16, median DFS was 23 (1-59) months; In patients with NAR>16, median DFS was 21 (4-54) (p0.003, HR 3.2, 95% CI 1.4-7.3 ). A statistically significantly lower recurrence was observed in the patient group with NAR ≤16 (p<0.001, HR 2.03, CI 95% 1.2-3.2). A statistically significant lower exitus was seen in the patient group with NAR ≤16 (p0.040, HR 1.7, CI 95% 0.89-3.5). Conclusion: Consistent with the literature in our study, significantly higher DFS and lower recurrence and death rates were observed in low NAR scores.